2022
DOI: 10.1002/anie.202112640
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stable and Reactive Platinum Single Atoms on Oxygen Plasma‐Functionalized CeO2 Surfaces: Nanostructuring and Peroxo Effects

Abstract: Atomically dispersed precious metals on oxide supports have recently become increasingly interesting catalytic materials. Nonetheless, their non-trivial preparation and limited thermal and environmental stability constitutes an issue for their potential applications. Here we demonstrate that an oxygen plasma pre-treatment of the ceria (CeO 2 ) surface serves to anchor Pt single atoms, making them active and resistant towards sintering in the CO oxidation reaction. Through a combination of experimental results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 43 publications
1
28
0
Order By: Relevance
“…Color code: Ce, gold; O, red; Pt, green; peroxo O 2 2– , pink. Reproduced with permission from ref . Copyright 2022 Wiley-VCH GmbH under CC-BY license ().…”
Section: Ceria (Ceo2)mentioning
confidence: 99%
“…Color code: Ce, gold; O, red; Pt, green; peroxo O 2 2– , pink. Reproduced with permission from ref . Copyright 2022 Wiley-VCH GmbH under CC-BY license ().…”
Section: Ceria (Ceo2)mentioning
confidence: 99%
“…The surface functionalization of CeO 2 can boost thermal stability and catalytic activity of Pt/CeO 2 in CO oxidation. The oxygen plasma pre-treatment on CeO 2 surface has been demonstrated to serve as an effective strategy ( Wan W. et al, 2022 ), which led to two crucial modifications of CeO 2 surface: 1) surface restructuring, surface roughening that suppressing the diffusion and aggregation of Pt atoms; 2) a significant amount of surface peroxide (O 2 2− ) powerfully anchoring Pt single atoms. These features are favor of a dense and uniform distribution of active Pt single atoms to boost CO oxidation.…”
Section: Applications Of Single-atom Catalysts For Air Pollutant Removalmentioning
confidence: 99%
“…26,[29][30][31] After O 2 plasma treatment, surface nanostructures and surface peroxo (O 2 2− ) species were formed, which favour the uniform and dense distribution of isolated strongly bonded Pt 2+ atoms. 32 Chae et al 33 also found that the discharge parameters (discharge power and time) of plasma effected the kinetics of the TiO 2 catalyst. Therefore, more and further research is necessary to study how the plasma discharge parameters (discharge power, time, and gas type) affect the catalyst resulting in the different performance of the catalyst.…”
Section: Introductionmentioning
confidence: 97%